IDH mutations may not preclude distant, trans-tentorial spread in gliomas: a case report and review of the literature. Issue 1 (December 2016) - Hong, Christopher; Hsieh, Jason; Edwards, Nancy; Ray-Chaudhury, Abhik; Zaghloul, Kareem
Abstract Background IDH mutations have been demonstrated to confer prolonged survival in patients suffering from gliomas, but the mechanisms underlying the improved prognosis are unclear. While some studies have attributed these observations to an enhanced sensitivity to genotoxic therapies, others have postulated that IDH-mutated gliomas exhibit less aggressive intrinsic biological behavior, including the propensity to invade distant sites. Although most gliomas recur local to the site of initial presentation, some tumors demonstrate distant recurrence, the vast majority of which involve the contralateral hemisphere. Trans-tentorial spread has been described once before, in which a supratentorial glioblastoma was reported to recur infratentorially in the cerebellum. Case presentation We describe a patient who underwent surgical resection, followed by adjuvant radiation and temozolomide of a World Health Organization (WHO) III anaplastic astrocytoma in the right temporal lobe, exhibiting an IDH1 (R132H) mutation. Twenty-two months after surgery, he developed a second lesion, located in the right cerebellum, suspicious for recurrent tumor versus radiation necrosis. A second surgery was performed, and pathology demonstrated recurrent tumor, consistent with IDH1-mutated anaplastic astrocytoma. Conclusions This is the first example of trans-tentorial spread in an IDH-mutated glioma, suggesting that despite improved survival, IDH mutations may not preclude gliomas from exhibiting the ability to invade distant sites of the brain.